APPROACHES TO THE IMPLEMENTATION OF ICT USE IN THE EDUCATIONAL PROCESS OF ECONOMIC SPECIALISTS - Vdovychyn, Тетяна (Journal of Information Technologies in Education (ITE), 2022)
Informatization of public life is closely related to the use of ICT, which promotes the development of automated information systems, software products for specific users, as well as new generation systems based on artificial intelligence, spatial operating systems, combining real and virtual worlds, augmented reality, etc. The use of ICT makes it possible to solve applied problems in a particular field, facilitates the functional responsibilities of employees, automates routine work, changes and optimizes management principles, and more. The choice of ICT tools to solve specific tasks in various firms, government agencies, organizations, etc. depends on the level of ICT competence of a particular employee. This study focuses on the use of ICT in the educational process, which significantly enhances motivation to learn, successful integration into modern society without any psychological barriers, development of creative potential and empowerment for educational services. In particular, the article focuses on the process of training future specialists in economics in higher education institutions (HEIs) using ICT and analyzes the application of these technologies in reporting, control, analysis of institutions, automation of document management in enterprises, simplification of accounting and more. The article demonstrates the practical implementation of ICT to create a timesheet using the capabilities of the VBA programming environment, which greatly simplifies accounting, saves time, automates and diversifies activities in the enterprise, promotes cost-effective construction and reliability of current and reporting data. Based on this study, the algorithm for creating a timesheet at the enterprise using VBA programming environment is described, in particular: entering the list of employees, choosing the name of the month of the current year, the number of days in the month (including working and weekends), choosing employees and entering information on the days worked by them, calculation of the number of days worked and unworked days for each individual employee of the enterprise, viewing and printing the completed report card, as well as making all necessary changes to the input data. The interface of the developed timesheet can be completely adapted, customized to the needs of a particular user.